The West German Study Group Breast Cancer Intrinsic Subtype study: a prospective multicenter decision impact study utilizing the Prosigna assay for adjuvant treatment decision-making in estrogen-receptor-positive, HER2-negative early-stage breast cancer. (2nd July 2016) - Wuerstlein, R.; Sotlar, K.; Gluz, O.; Otremba, B.; von Schumann, R.; Witzel, I.; Schindlbeck, C.; Janni, W.; Schem, C.; Bauerfeind, I.; Hasmueller, S.; Tesch, H.; et al.
Abstract: Purpose : The West German Study Group (WSG) Breast Cancer Intrinsic Subtype (BCIST) study was designed to assess the influence of Prosigna † gene signature assay results on physicians' adjuvant treatment recommendations by determining the extent of change in pre-test treatment recommendations following assay results. Secondary objectives were to assess the influence of Prosigna results on physicians' confidence in their therapeutic recommendations and on patients' decisional conflict status, anxiety levels, and functional status.Methods : This prospective, observational, decision impact study enrolled consecutive postmenopausal patients with estrogen-receptor (ER)-positive, HER2-negative, lymph-node-negative early-stage breast cancer in 11 centers in Germany. Physicians based their pre-test adjuvant treatment recommendations on standard clinico-pathological parameters. Tumor specimens were assayed using the Prosigna test in a WSG central pathology laboratory following manufacturer's guidelines. An independent pathology laboratory performed subsequent Prosigna assays on tumor sections to assess assay result concordance with the central laboratory. Physicians completed treatment confidence questionnaires prior to and after receiving Prosigna test results. Patients completed standardized questionnaires on decisional conflict, anxiety, and health status both before and after Prosigna testing.Results : The present study population consisted predominantly of low-to-intermediate risk patients ( N  = 198). Prosigna had 29.3% discordance in intrinsic subtyping with local immunohistochemistry test results. After Prosigna test results, a change in the adjuvant therapy recommendation occurred in 36 (18.2%) patients; 22 (11.1%) patients switched from no chemotherapy to chemotherapy. After Prosigna test results, physicians expressed increased confidence in their prognostic assessment in 87.9% of patients, and increased confidence in their treatment recommendation in 89.4%. Patients reported improved anxiety and emotional/functional well-being after receiving Prosigna test results.Conclusions : Use of the Prosigna assay led to a change in 18.2% of adjuvant treatment decisions. Prosigna testing was associated with increased patient and physician confidence in treatment decisions, and with decreased patient anxiety and improved well-being. Any comparison of the therapeutic decision-making impacts of different genomic assays must account for potential confounding factors.